The Human Tau Interactome: Binding to the Ribonucleoproteome, and Impaired Binding of the Proline-to-Leucine Mutant at Position 301 (P301L) to Chaperones and the Proteasome - Gunawardana, C. Geeth; Mehrabian, Mohadeseh; Wang, Xinzhu; Mueller, Iris; Lubambo, Isabela B.; Jonkman, James E.N.; Wang, Hansen; Schmitt-Ulms, Gerold (Molecular & cellular proteomics, 2015)
The tau protein is central to the etiology of several neurodegenerative diseases, including Alzheimer's disease, a subset of frontotemporal dementias, progressive supranuclear palsy and dementia following traumatic brain injury, yet the proteins it interacts with have not been studied using a systematic discovery approach. Here we employed mild in vivo crosslinking, isobaric labeling, and tandem mass spectrometry to characterize molecular interactions of human tau in a neuroblastoma cell model. The study revealed a robust association of tau with the ribonucleoproteome, including major protein complexes involved in RNA processing and translation, and documented binding of tau to several heat shock proteins, the proteasome and microtubule-associated proteins. Follow-up experiments determined the relative contribution of cellular RNA to the tau interactome and mapped interactions to N- or C-terminal tau domains. We further document that expression of P301L mutant tau disrupts interactions of the C-terminal half of tau with heat shock proteins and the proteasome. The data are consistent with a model whereby a higher propensity of P301L mutant tau to aggregate may reflect a perturbation of its chaperone-assisted stabilization and proteasome-dependent degradation. Finally, using a global proteomics approach, we show that heterologous expression of a tau construct that lacks the C-terminal domain, including the microtubule binding domain, does not cause a discernible shift of the proteome except for a significant direct correlation of steady-state levels of tau and cystatin B.